O impacto dos ciclos político econômicos nos retornos e na volatilidade do Ibovespa - Locatelli, André (2017)
The present dissertation aims, through the theories of economic political cycles, to investigate if they influence the returns and volatility of the Ibovespa, index of the São Paulo Stock Exchange. The four main theories dealing with the theme, Traditional Party Theory, Traditional Opportunist Theory, Rational Party Theory and Opportunistic Rational Theory will be addressed. The data used will be the Ibovespa daily returns and the daily returns of the S & P 500, one of the main indices of the North American stock market and that will serve to capture the changes of the external stock market. In order to calculate the influence of economic policy cycles on the returns and volatility of the Ibovespa, the ARCH and GARCH econometric models have been used, which have been widely used in such works and have been shown to be consistent in the estimation of time series. The ARCH model had better results for the estimated model. Four different Dummy variables, each representing a different time period, were tested to determine whether economic policy cycles influenced Ibovespa returns and volatility in those periods. At the 5% significance level, abnormal returns in the periods included in the Dummy variables were not found nor was there statistically significant change in variance in the same periods. At a significance level of 10%, the influence of economic policy cycles on the volatility of the Ibovespa in the period of 180 days, ranging from 12 months to 6 months before the presidential elections, was found.